ToyAssembler: Sewing Patterns into a 3D Toy by Automatic Pre-Positioning. (October 2022) - Jin, Yinghan; Li, Jituo; Zhang, Dongliang
Abstract: In this paper, we present an efficient tool ToyAssembler for sewing 2D patterns into 3D plush/inflatable toys. To simulate a 3D toy from 2D patterns, it is necessary to arrange 2D patterns at appropriate positions in 3D space according to their sewing relations. However, manual pre-positioning is time-consuming and hard to achieve satisfactory results. ToyAssembler provides an automatic pattern pre-positioning algorithm. Firstly, a sewing relation graph is constructed based on sewing correspondences, then patterns are divided into several groups by decomposing the graph. Secondly, patterns of each group are wrapped onto a cylinder, and then all groups of wrapped patterns are assembled to obtain the final 3D patterns with appropriate positions for sewing. At last, pre-positioned patterns are sewn into a 3D toy using physically-based simulation. Experiment results demonstrate that patterns are reasonably pre-positioned and satisfactory toy models can be created. Our approach significantly reduces the time and effort of rebuilding toy models from 2D patterns. Highlights: A novel method is presented for sewing 2D patterns into 3D plush/inflatable toy models by automatic pre-positioning. A pattern grouping method is proposed by decomposing a sewing relation graph. A wrapping and assembling method is proposed to place patterns at appropriate positions for sewing simulation.